2008
DOI: 10.1152/ajpheart.00129.2008
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol accelerates endothelial healing through the retrograde commitment of uninjured endothelium

Abstract: Although the accelerative effect of 17␤-estradiol (E2) on endothelial regrowth has been clearly demonstrated, the local cellular events accounting for this beneficial vascular action are still uncertain. In the present work, we compared the kinetics of endothelial healing of mouse carotid arteries after endovascular and perivascular injury. Both basal reendothelialization as well as the accelerative effect of E 2 were similar in the two models. Three days after endothelial denudation, a regenerative area was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…thelial cells that have maximal migration from the line of injury spanning the carotid obtained with the software ZEISS LSM image Borswer v.3.1 (48).…”
Section: Morphometric and Immununohistochemical Analyses Of Fatty Strmentioning
confidence: 99%
“…thelial cells that have maximal migration from the line of injury spanning the carotid obtained with the software ZEISS LSM image Borswer v.3.1 (48).…”
Section: Morphometric and Immununohistochemical Analyses Of Fatty Strmentioning
confidence: 99%
“…The perivascular carotid electric injury was performed as previously described. 11,14 Briefly, surgery was carried out with a stereomicroscope (Nikon A, Mice were ovariectomized at 4 weeks of age and implanted or not with a pellet releasing E2. Carotid injury was performed at 6 weeks of age.…”
Section: Mouse Carotid Injurymentioning
confidence: 99%
“…17␤-estradiol (E2), the main endogenous estrogen, exerts many vascular protective effects by increasing basal production of endothelial nitric oxide (NO), 13 accelerating reendothelialization 12,14 or inhibiting neointima formation. 15 We previously demonstrated that E2 accelerates reendothelialization in a mouse model of perivascular carotid injury, through estrogen receptor (ER) ␣ but not ER␤.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The endothelium exerts these actions through the release of such vasoactive compounds as prostacyclin, thromboxane A 2 , nitric oxide (NO), bradykinin, endothelin, angiotensin, and free radicals that control the functions of vascular smooth muscle cells and of circulating blood cells (Ross, 1999;Vapaatalo & Mervaala, 2001). The integrity and functionality of the arterial endothelium play a crucial role in the physiology of circulation (Filipe et al, 2008) and, as a consequence, in preventing the development of cardiovascular diseases, whose genesis is currently considered a consequence of the anatomical and functional disruption of the endothelium (Spyridopoulos et al, 1997). When the ability of the endothelial cells to release relaxing is reduced, and in particular if the propensity to produce contractile factors is enhanced, endothelial dysfunction appears as a first step in the sequence of events that leads to atherosclerosis and coronary disease.…”
Section: Introductionmentioning
confidence: 99%